2021
DOI: 10.1007/s00210-021-02083-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and beyond—a tribute to Manfred Göthert (1939-2019)

Abstract: Manfred Göthert, who had served Naunyn-Schmiedeberg’s Arch Pharmacol as Managing Editor from 1998 to 2005, deceased in June 2019. His scientific oeuvre encompasses more than 20 types of presynaptic receptors, mostly on serotoninergic and noradrenergic neurones. He was the first to identify presynaptic receptors for somatostatin and ACTH and described many presynaptic receptors, known from animal preparations, also in human tissue. In particular, he elucidated the pharmacology of presynaptic 5-HT receptors. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 324 publications
(462 reference statements)
0
5
0
Order By: Relevance
“…Presynaptic CB 1 -Rs leading to inhibition of atrial NA release have also been identified in vitro in atrial tissue from humans [ 168 ], guinea pigs [ 177 ] and rats [ 178 ]. Presynaptic facilitatory CB 1 -Rs cannot be expected, since CB 1 -Rs are G i/o protein-coupled and only G s and G q protein-coupled receptors lead to facilitation of neurotransmitter release [ 208 ]. The other three receptor entities activated by THC, i.e., CB 2 , GPR18 [ 177 ] and GPR55, do not serve as presynaptic receptors.…”
Section: Tachycardia—mechanismsmentioning
confidence: 99%
“…Presynaptic CB 1 -Rs leading to inhibition of atrial NA release have also been identified in vitro in atrial tissue from humans [ 168 ], guinea pigs [ 177 ] and rats [ 178 ]. Presynaptic facilitatory CB 1 -Rs cannot be expected, since CB 1 -Rs are G i/o protein-coupled and only G s and G q protein-coupled receptors lead to facilitation of neurotransmitter release [ 208 ]. The other three receptor entities activated by THC, i.e., CB 2 , GPR18 [ 177 ] and GPR55, do not serve as presynaptic receptors.…”
Section: Tachycardia—mechanismsmentioning
confidence: 99%
“…These two scientists had a major impact on the major research topics of the journal for decades and the contribution of cities to the journal (see discussion below). Starke and Göthert also provided service to the journal as editors (Starke 1998 ; Bönisch et al 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…“Immunopharmacology” also rose to become the second most represented category in 2020. The contribution of neurotransmitter pharmacology to Naunyn–Schmiedeberg’s Archives of Pharmacology declined substantially over the decades, a major reason being that top contributors to the field retired or even passed away (Bönisch et al 2021 ). The importance of Naunyn–Schmiedeberg’s Archives of Pharmacology as a general mechanistic journal dedicated to molecular mechanisms of drug action also declined over the decades (“Introduction and Pharmacodynamics”).…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of the neurotransmitter serotonin, in 1949 by Maurice Rapport, began a branch of research about this molecule [ 8 , 9 , 10 , 11 ]. Abbreviated as 5-HT, for the molecule 5-hydroxytryptamine, serotonin is “involved in numerous diseases of the (central nervous system) CNS (e.g., depression, anxiety, schizophrenia, obsessive-compulsive disorders, addiction, Parkinson’s disease) and peripheral organs (e.g., gastrointestinal disorders, cardiac arrhythmia, hypertension)" [ 12 ].…”
Section: Reviewmentioning
confidence: 99%